Analysis of Consumer Decisions in Purchasing Snack Products at the Store of Rumah Cemilan Kendari in Kadia District, Kendari City - Rosmida Teke; Weka Gusmiarty Abdullah; Rosmawaty Rosmawaty (International Journal of Economics, Business and Innovation Research, 2023)
This study aims to (1) describe the consumer decision-making process in purchasing snack products at the store of Rumah Cemilan Kendari in Kadia District, Kendari City, and (2) find out the factors that influence consumer decisions in purchasing snack products at the store of Rumah Cemilan Kendari in Kadia District, Kendari City. The determination of the location of this study was carried out purposively. The population of this study was an unknown number of snack food consumers. The sample of this study was determined by accidental sampling technique, and the number of samples was 50 respondents data analysis using descriptive analysis. The results showed that (1) when making consumer decisions on snack products at the store of Rumah Cemilan Kendari, consumers know the need to snack with their families. Hence, they search for information about snack products that meet their requirements. Most get information from friends where the focus of attention is affordable prices, product durability, and product flavour variants. (2) Factors that consumers consider in purchasing decisions for snack products at The store of Rumah Cemilan Kendari are taste, low prices, and clean and comfortable store locations.